Proposta didattica in tempi di transizione energetica: il crimine idrocarburico - Francescangeli, Adriano (Chimica nella Scuola, 2023)
Chemistry teaching is receiving many contributions aimed at raising students’ awareness of our society’s need for an energy transition. This paper describes a phenomenon, hydrocarbon crime, which despite its relevance is scarcely known to the public and is often absent in debates on the transition to renewable sources. It also describes the socio-economic and environmental consequences of criminal infiltration in the supply and distribution of the hydrocarbons sector. Furthermore, it is emphasized that this epochal transition cannot be separated from a restoration of legality in the current context of the fossil fuel market. This paper is written for chemistry teachers with the aim of offering tools to allow them to include the topic of hydrocarbon crime in class discussions about energy transition.